Factors Related to Perceived Self-Efficacy in Coping with Labor Pain in Primiparous Pregnant Women - Sinlatamkij , Chanokpron; Phuangprasonka, Rachada (Journal of The Royal Thai Army Nurses, 2022)
The objective of this descript study was to examine factors related to Perceived Self-Efficacy in Coping with Labor Pain Among Primiparous Women. Research participants were 128 first-time pregnant women attending ante natal care clinic at Samutprakarn hospital. They were recruited in the study by simple random sampling. Data were collected by using questionnaires of including Personal record form, Childbirth self-efficacy inventory Questionnaire, Attitude towards Childbirth Questionnaire, Labor Social support Questionnaire and Thai Version of Childbirth Self-efficacy Inventory. Data were analyzed by using descriptive statistics and Pearson product moment correlation coefficients. The results showed that there was statistically significant positive correlation between education (r = .069, p = .438), status (r = .029, p = .745), length time of labor (r = .074, p = .405), Attitude towards Childbirth (r = .046, p = .604), and Social support at the alpha level .05.